Emotional difficulties, coping strategies, and help-seeking patterns among Czech perinatal women - Banasova, Renata; Noskova, Eliska; Vodickova, Renata; Hasto, Jozef; Sebela, Antonin (Midwifery, 2023)
OBJECTIVE: To understand both, women ́s perception of emotional difficulties in perinatal period and their related coping strategies. Further, we mapped and analysed help-seeking patterns utilized by these women to overcome their emotional difficulties. This study serve as an important piece of information for women-centred innovations in perinatal mental health care in Czechia, and more broadly in the region of Central and Eastern Europe. DESIGN: A qualitative study with an exploratory and descriptive approach using thematic analysis. SETTING: Online survey consisting of open-ended questions mapping women ́s perception of emotional difficulties in perinatal period and their related coping strategies and help-seeking patterns. PARTICIPANTS: Two hundred women self-reporting emotional difficulties in perinatal period, from whom 108 (54 %) stated that they had sought professional help with their emotional difficulties. FINDINGS: Two themes were identified in the analysis of women ́s perception of emotional difficulties including Experience of symptoms of mental disorders, and Mother-child relationship. Three themes were identified in the analysis of women ́s coping with these difficulties (Personal resources, External resources, and No coping strategy used). Four themes were identified in the analysis of help seeking patterns utilized by study participants (Mental health specialists, Physicians of the first line of contact, Midwifes, and Peer consultants). KEY CONCLUSIONS: Emotional difficulties of perinatal women stemmed in both, general symptoms of mental disorders and specific concerns connected to mother-child relationship. Therefore, the perinatal mental health services should cover both topics, preferably by a multidisciplinary team. Women search information about perinatal mental health, so thus, easy to reach valid resources are needed. Finally, Czech perinatal women experiencing emotional difficulties utilize various help-seeking patterns. Some of them naturalistically utilize integrated stepped care even when it is not systematically established.
Keywords: Adaptation, Psychological; Mental Health; Pregnancy; Mental Disorders; lidé; Mental Health Services; kvalitativní výzkum; adaptace psychologická; ženské pohlaví; duševní poruchy; Humans; Qualitative Research; služby péče o duševní zdraví; Female; těhotenství; duševní zdraví